Enhancing Elementary Students' Numeracy Skills Through The Concrete Pictorial Abstract (CPA) Approach - Suryaningsih, Tri; Nisa, Khoerun; Widiyanto, Rohmat; Latip, Asep Ediana; Siron, Yubaedi (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
This study investigates the impact of the Concrete-Pictorial-Abstract (CPA) method on fifth-grade students' SDN Cipayung 02 numeracy skills. In response to low numeracy performance on national examinations such as PISA, TIMSS, and Indonesia National Assessment Programme, as well as classroom observations emphasizing standard teaching approaches' limitations, this study investigates CPA as an alternate instructional strategy. The study used a posttest-only control group structure and a quasi-experimental methodology. Two randomly chosen classes make up the sample; one is the experimental group, and the other is the control. Data were obtained by testing, and the Independent Sample T-Test in SPSS Version 29 was used for analysis. Higher post-test scores in the experimental group (mean score of 70.32) than in the control group (mean score of 45.86) demonstrate that the CPA strategy significantly enhances students' numeracy skills when compared to traditional teaching approaches. The CPA technique, which goes through concrete, pictorial, and abstract stages, promotes a stronger mental understanding and practical application of mathematical principles. This study emphasizes the CPA approach's effectiveness in promoting numeracy literacy and suggests its widespread implementation in mathematics instruction. This study shows that CPA can be applied in mathematics learning by gradually using concrete objects, images, and symbols to improve students' understanding. Teachers need to be trained in using CPA through professional training and developing more interactive teaching modules. Numeracy assessments should also be adapted to problem-based formats and visual representations to suit this approach better. Education policies can adopt CPA in the national curriculum to improve numeracy literacy and international assessment results.